Dampak Pandemi Coronavirus Disease Terhadap Kesehatan Mental Masyarakat - Lilis Raodatul Jannah; Basmalah Harun (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Background the increase in the number of Covid-19 cases occurred quickly and spread in various countries in a short time. The impact of coronavirus disease pandemic on people's mental health is in the form of stress, anxiety, depression, and trauma. Aim to know the impact of coronavirus disease pandemic on people's mental health. Method quantitative Descriptive with a Literature Review Approach. Data sources are obtained from search results and article selection using PubMed databases and google scholar. Four articles were identified as meeting the criteria: 1) a sample of people experiencing mental health disorders due to covid-19; 2) issued in 2019-2021; 3) speak English and Indonesian; 4) have full text; 5) Analysis using data maps extracted in grid synthesis tables including authors, year of publication, Country, purpose, sample size, research design, results, and conclusions. Results showed that the impact of the covid-19 pandemic on mental problems is that people experience psychological disorders in the form of anxiety, stress, depression, and trauma. Conclusion coronavirus disease has a great impact on people's mental health.